Between virtue and risk: ESG dynamics and the strategic role of gender-diverse boards - Qawasmeh, Rasha; Samara, Husni; Alslaibi, Naji; Farha, Enas Kamal Khaled Abu; Elamer, Ahmed A. (John Wiley and Sons, 2026)
This study examines the asymmetric effects of environmental, social, and governance (ESG) performance and ESG controversies on firm performance and investigates the moderating role of executive gender diversity. Using a panel of 561 non-financial firms from 14 European countries over the period 2014–2023, we employ a two-stage least squares (2SLS) approach to address endogeneity concerns. Firm performance is measured using both market-based (Tobin's Q) and accounting-based (ROA) indicators. The results show that ESG performance is positively associated with firm value, whereas ESG controversies exert significant negative effects, reflecting the reputational and financial costs of ESG failures. Importantly, executive gender diversity strengthens the positive performance implications of ESG engagement and mitigates the adverse effects of ESG controversies, although gender diversity in isolation does not uniformly enhance performance. Board-level governance characteristics operate as contextual mechanisms, exhibiting divergent effects across market- and accounting-based performance measures. By distinguishing between ESG performance and ESG controversies and by conceptualizing executive gender diversity as a contingent executive-level attribute, this study contributes to Corporate Social Responsibility, Institutional, and Upper Echelons theories. The findings highlight the importance of executive-level diversity and governance alignment in translating ESG engagement into sustainable firm value.